A Comprehensive Radiologic Review of Shoulder Girdle Trauma - Nasir, Muhammad Umer; Alsugair, Faisal; Sheikh, Adnan; Ouellette, Hugue; Munk, Peter; Mallinson, Paul (Seminars in Musculoskeletal Radiology, 2022)
Radiologic knowledge of different fracture patterns involving the shoulder girdle is an important tool to generate clinically relevant reports, identify concomitant injuries, guide management decisions, and predict and minimize complications, such as nonunion, osteoarthritis, osteonecrosis, and hardware failure. Complex unstable injuries like scapulothoracic dissociation can also occur because of shoulder girdle trauma. Management options may vary from conservative to surgical, depending on the fracture type and patient factors. Injuries around the shoulder girdle can involve the glenohumeral articulation, scapula, superior shoulder suspensory complex, acromioclavicular joints, and scapulothoracic articulation.
Keywords: shoulder girdle; trauma; musculoskeletal; radiology; fractures